2009
DOI: 10.1111/j.1365-3156.2009.02376.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with death among HIV‐uninfected TB patients in Thailand, 2004–2006

Abstract: Summaryobjectives In countries with both TB and human immunodeficiency virus (HIV) epidemics, HIV is known to be the most powerful risk factor for death during tuberculosis (TB) treatment. Few recent studies have evaluated risk factors for death among HIV-uninfected TB patients in these countries. We analysed data from a multi-province demonstration project in Thailand to answer this question.method We prospectively collected data from HIV-uninfected TB patients treated for TB in four provinces and the nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
(30 reference statements)
5
6
1
Order By: Relevance
“…The rate of successful treatment outcome was also lowest in the rifampicin resistant group. The current findings are consistent with the finding reported in Tak province, Thailand, and also concurrent with existing literature on TB drug resistance and higher death rate ( Amnuaiphon et al, 2009 ; Hemhongsa et al, 2008 , WHO, 2010 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The rate of successful treatment outcome was also lowest in the rifampicin resistant group. The current findings are consistent with the finding reported in Tak province, Thailand, and also concurrent with existing literature on TB drug resistance and higher death rate ( Amnuaiphon et al, 2009 ; Hemhongsa et al, 2008 , WHO, 2010 ).…”
Section: Discussionsupporting
confidence: 93%
“…Globally, patients with MDR-TB have lower cure rates and higher mortality rates than patients with drug-susceptible TB ( Mitnick et al, 2003 ; Nathanson et al, 2006 ). This is also true in Thailand, where MDR-TB has a significant association with mortality rate both in HIV-infected and HIV-uninfected TB patients ( Maranetra, 1996 ; Amnuaiphon et al, 2009 ; Sanguanwongse et al, 2008 ).…”
Section: Introductionmentioning
confidence: 82%
“…We have demonstrated that older age contributes to an increase in relative risk of death independent of HIV status, a finding consistent with previous studies [10]. This may be due to concomitant pathology, less physical reserves or it may reflect an increasing frequency of non-TB causes of death.…”
Section: Discussionsupporting
confidence: 91%
“…Bacteriological factors related to causal organism like culture positivity, drug resistance, and multidrug-resistant TB (MDR-TB) were not significant factors in the current study. However, previous studies in Thailand and Europe reported that MDR-TB was a significant risk for overall TB death 7,19. The different finding could be due to a different time point of analysis and low level of MDR-TB prevalence in Chiang Rai.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies in various regions of the world reported high risk for elderly TB patients, but the risk was not specified for death in the first month 7,11,1419. Recently, analysis of TB surveillance data from 15 European Union (EU) countries during 2002–2004 reported that advancing age and resistance to isoniazid and rifampicin were the strongest risks of TB death 19.…”
Section: Discussionmentioning
confidence: 99%